Does Regulation Trigger Volatility? : Empirical Evidence from the Bitcoin, Ethereum, and Ripple Markets in Indonesia - Maulana, Ilham (The International Journal of Financial Systems, 2026)
The implementation of PMK 50/2025 marks a pivotal moment in Indonesia’s digital asset fiscal landscape through the introduction of a 0.21% final income tax and the formal transition of oversight to the Financial Services Authority (OJK). This study empirically examines whether these regulatory changes triggered volatility shocks in three major cryptocurrencies: Bitcoin (BTC), Ethereum (ETH), and Ripple (XRP). Using an ARMA(1,1)-eGARCH(1,1) model with Student-t distribution and USD returns as a global market control, we estimate conditional daily volatility over a three-period framework: Pre Announcement, Post-Announcement, and Post-Implementation. Hypothesis testing employs the Wilcoxon Rank-Sum Test (Mann-Whitney U Test), supplemented by dummy regression with Newey-West HAC standard errors, and structural break tests. The primary results reveal no statistically significant change in conditional volatility following PMK 50/2025 for all three assets (Mann Whitney U, all p>0.05). Notably, the dummy regression identifies a statistically significant reduction in Ethereum’s conditional volatility post-implementation (β=−0.000287, p=0.028), corroborated by a structural break toward stability. All assets exhibit a significant positive asymmetry (γ>0), indicating that positive shocks drive greater volatility than negative shocks — a distinctive crypto-market characteristic. Robustness checks using sGARCH(1,1) confirm the main findings. Overall, the results indicate that PMK 50/2025 was not associated with a statistically significant increase in conditional volatility during the observed event windows. These findings should be interpreted as evidence on conditional volatility response only, and do not constitute a comprehensive assessment of market quality, liquidity, or overall resilience.